2023
DOI: 10.3390/ma16124218
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Sulfur@g-C3N4 and CuS@g-C3N4 Catalysts for Hydrogen Production from Sodium Borohydride

Abstract: In this work, the S@g-C3N4 and CuS@g-C3N4 catalysts were prepared via the polycondensation process. The structural properties of these samples were completed on XRD, FTIR and ESEM techniques. The XRD pattern of S@g-C3N4 presents a sharp peak at 27.2° and a weak peak at 13.01° and the reflections of CuS belong to the hexagonal phase. The interplanar distance decreased from 0.328 to 0.319 nm that facilitate charge carrier separation and promoting H2 generation. FTIR data revealed the structural change according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…The boron atom in BH 3 OCH 3 is electron-deficient. It can accept an electron from the CH 3 O group, which results in the formation of BH 3 OCH 3 [92].…”
Section: Resultsmentioning
confidence: 99%
“…The boron atom in BH 3 OCH 3 is electron-deficient. It can accept an electron from the CH 3 O group, which results in the formation of BH 3 OCH 3 [92].…”
Section: Resultsmentioning
confidence: 99%
“…The surface area of MCN-UF-3.5 was larger than that of g-C3N4 (10.3 m 2 •g -1 ) by 3.74 times. The previous studies reported that increased specific surface area is helpful to enhance photocatalytic performance (Alshammari et al 2023). Therefore, the doping of CDs increased photocatalysts' specific surface area, making the 2-dimensional structure turn into the 3dimensional structure (Zhu et al 2017).…”
Section: Morphology and Structure Characterizationmentioning
confidence: 99%
“…However, a noble metal cannot be widely applied due to its expensive and scarce properties. Therefore, various non-precious transition metals (Fe, 93 Co, [94][95][96][97] Ni, 98 and Cu 99 ) and metal oxide/boride/ 2 of 41 -cMat phosphide [100][101][102][103][104][105] catalysts have been used as effective active species for catalyzing the hydrolysis of SB. Among them, Cu-based catalysts with relatively high catalytic activity have been extensively studied in the past few years.…”
Section: Sodium Borohydridementioning
confidence: 99%